(untitled) (Czech Journal of International Relations, 1966)
Recently, in the research of international relations and political science, increased attention has been paid to issues of culture. This is not because these fields of science "fashionably" focus in this direction, but it largely reflects the fact that many countries increased attention to the role of culture in creating their foreign policy line and in enforcing it. Undoubtedly, it is related to the overall development of the international situation, where the policy of peaceful coexistence is increasingly being promoted against the influence of imperialist countries. If the influence of military and power factors in world politics weakens, the space for the action of other factors, especially culture, undoubtedly expands. The possibility of eliminating wars from international relations offers the perspective of peaceful coexistence, and here the exchange of cultural values ​​comes to the fore.